Comparison Of The Gut Microbiota In Different Age Groups In China - Yan, Hang; Qin, Qian; Yan, Su; Chen, Jingfeng; Yang, Yang; Li, Tiantian; Gao, Xinxin; Ding, Suying (Frontiers in Cellular and Infection Microbiology, 2022)
Aging is now the most profound risk factor for almost all non-communicable diseases. Studies have shown that probiotics play a specific role in fighting aging. We used metagenomic sequencing to study the changes in gut microbes in different age groups and found that aging had the most significant effect on subjects’ gut microbe structure. Our study divided the subjects (n=614) into two groups by using 50 years as the age cut-off point for the grouping. Compared with the younger group, several species with altered abundance and specific functional pathways were found in the older group. At the species level, the abundance of Bacteroides fragilis, Bifidobacterium longum, Clostridium bolteae, Escherichia coli, Klebsiella pneumoniae, and Parabacteroides merdae were increased in older individuals. They were positively correlated to the pathways responsible for lipopolysaccharide (LPS) biosynthesis and the degradation of short-chain fatty acids (SCFAs). On the contrary, the levels of Barnesiella intestinihominis, Megamonas funiformis, and Subdoligranulum unclassified were decreased in the older group, which negatively correlated with the above pathways (p-value<0.05). Functional prediction revealed 92 metabolic pathways enriched in the older group significantly higher than those in the younger group (p-value<0.05), especially pathways related to LPS biosynthesis and the degradation of SCFAs. Additionally, we established a simple non-invasive model of aging, nine species (Bacteroides fragilis, Barnesiella intestinihominis, Bifidobacterium longum, Clostridium bolteae, Escherichia coli, Klebsiella pneumoniae, Megamonas funiformis, Parabacteroides merdae, and Subdoligranulum unclassified) were selected to construct the model. The area under the receiver operating curve (AUC) of the model implied that supplemented probiotics might influence aging. We discuss the features of the aging microbiota that make it more amenable to pre-and probiotic interventions. We speculate these metabolic pathways of gut microbiota can be associated with the immune status and inflammation of older adults. Health interventions that promote a diverse microbiome could influence the health of older adults.